2005
DOI: 10.1111/j.1742-4658.2004.04537.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in the hippocampus after pilocarpine‐induced status epilepticus in Wistar rats

Abstract: Status epilepticus (SE) is a neurological emergency with an associated mortality of 10-12% [1]. Pilocarpine-induced seizure models have provided information on the behavioral and neurochemical characteristics associated with seizure activity [2,3]. Other studies suggest permanent changes in different biochemical systems during SE. An increase in lipid peroxidation, a decrease in GSH content, and excessive free radical formation may occur during SE induced by pilocarpine [4,5].This model can be used to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
102
1
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(131 citation statements)
references
References 37 publications
14
102
1
3
Order By: Relevance
“…There is clinical and experimental evidence of reduced oxygen availability after status epilepticus. Evidence for the role of free radicals in status epilepticus has been found by using enzymatic and nonenzymatic antioxidant treatment for the protection against seizures and for status epilepticus -induced neuronal damage (Freitas et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…There is clinical and experimental evidence of reduced oxygen availability after status epilepticus. Evidence for the role of free radicals in status epilepticus has been found by using enzymatic and nonenzymatic antioxidant treatment for the protection against seizures and for status epilepticus -induced neuronal damage (Freitas et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings showed that GFC, DMF, EAF, EE, or HE did not produce alterations in the hippocampus CAT activity, since they did not protect to the hippocampus from neuronal damage induced by lipid peroxidation products. It is unlikely that the unaltered CAT activity is related to the mechanisms involved in maintenance of oxidative stress (Freitas et al, 2005). These data suggest that hippocampus of rats pretreated with GFC, fractions, and extracts from P. insignis do not use CAT as the major free radical scavenging system.…”
Section: Discussionmentioning
confidence: 65%
“…As crises convulsivas induzidas pela pilocarpina também estão associadas a várias mudanças neuroquímicas no corpo estriado de ratos 2 . Essas crises convulsivas podem alterar a síntese, a liberação e/ou a biotransformação de vários neurotransmissores, entre eles do GABA e glutamato 3 , como também produzem mudanças na atividade de enzimas antioxidantes 4 .…”
Section: Introductionunclassified
“…Várias alterações na concentração da peroxidação lipídica, no conteúdo do nitrito, no nível da glutationa reduzida e na atividade antioxidante enzimática foram verificadas durante a fase aguda das crises convulsivas 4 . De modo geral, os radicais livres têm sido implicados na patogênese de várias doenças neurológicas, incluindo a epilepsia.…”
Section: Introductionunclassified